Micro–Nanostructure‐Assisted Luminescence in Perovskite Devices. Issue 12 (15th December 2021) - Tang, Ying-Yi; Shen, Yang; Wang, Jing-Kun; Qian, Xiao-Yan; Guo, Ming-Lei; Li, Yan-Qing; Tang, Jian-Xin
Abstract : Micro–Nanostructure‐Assisted Luminescence The micro‐nanostructure engineering provides an effective strategy for improving the luminescent characteristics of perovskite materials and optoelectronics. In article number 2100084, Yan‐Qing Li, Jian‐Xin Tang, and co‐workers summarize the recent developments of micro–nanostructure‐assisted optical manipulation approaches to enhance photo/electroluminescence of perovskite emitters, light‐outcoupling in light‐emitting diodes, and stimulated light emission for perovskite lasers.